2015
DOI: 10.1158/1535-7163.mct-14-0348
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Photodynamic Therapy Targeting Cancer Cells and Tumor-Associated Macrophages

Noriyuki Hayashi,
Hiromi Kataoka,
Shigenobu Yano
et al.

Abstract: Tumor-associated macrophages (TAM) in cancer stroma play important roles for cancer cell growth, invasion, angiogenesis, and metastases. We synthesized a novel photosensitizer, mannose-conjugated chlorin (M-chlorin), designed to bind mannose receptors highly expressed on TAMs. We evaluated the newly available photodynamic therapy (PDT) with M-chlorin against gastric and colon cancer. We evaluated PDT with Mchlorin for in vitro cytotoxicity and apoptosis induction in cancer cells compared with chlorin alone and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 46 publications
0
54
1
Order By: Relevance
“…Therefore, G-chlorin is a potential photosensitizer of PDT for treating gastric and colon cancer and GIST in vitro and in vivo [19, 20]. Furthermore, we found that PDT with mannose-conjugated chlorin displayed very strong anticancer effects [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, G-chlorin is a potential photosensitizer of PDT for treating gastric and colon cancer and GIST in vitro and in vivo [19, 20]. Furthermore, we found that PDT with mannose-conjugated chlorin displayed very strong anticancer effects [21]. …”
Section: Introductionmentioning
confidence: 99%
“…In an in vivo allograft model study, M-chlorin PDT showed the strongest antitumor effects. The number of TAMs in the cancer tissue after PDT was significantly decreased in the M-chlorin group compared to the other groups (chlorin and G-chlorin) (19).…”
Section: Targeting Tumor-associated Macrophages (Tams) In Cancer Tissmentioning
confidence: 72%
“…We observed the remarkable PDT effect with H 2 TFPC-SMan for in vitro and in vivo investigations in the previous report. 32 Thus, H 2 TFPCSMan has great potential for use as a PDT and a photodynamic diagnostic agent. …”
Section: Resultsmentioning
confidence: 99%
“…TAMs are known to specifically express abundant levels of CD206, a mannose receptor, 2931 which is also called the pattern-recognition receptor. We recently reported a remarkable PDT effect with a newly prepared mannose-conjugated chlorin (H 2 TFPCSMan = 5,10,15,20-tetrakis(4-(α-D-mannopyranosylthio)-2,3,5,6-tetrafluorophenyl)-2,3-(methano-(N-methyl)iminomethano)chlorin) designed to bind mannose receptors highly expressed on TAMs and evaluated PDT with H 2 TFPC-SMan for in vitro cytotoxicity and apoptosis induction in gastric and colon cancer cells 32 as compared with chlorin (H 2 TFPC = 5,10,15,20-tetrakis(pentafluorophenyl)-2,3-(methano(N-methyl)iminomethano)chlorin) alone and glucose-conjugated chlorin (H 2 TFPC-SGlc = 5,10,15,20-tetrakis(4-(β-D-glucopyranosylthio)-2,3,5,6-tetrafluorophenyl)-2,3-(methano(Nmethyl)iminomethano)chlorin). 17,18,2831 Here, we wish to report the detailed synthetic procedure of mannose-conjugated chlorin (H 2 TFPC-SMan) and its PDT effect in HeLa cells, including an X-ray crystal structure of 2,3,4,6-tetra-O-acetyl-1-S-acetyl-α-D-mannopyranose (AcManSAc), since no descriptions of any synthetic procedures were described in the previous report.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation